The Global Weak Solution for a Generalized Camassa-Holm Equation - Shaoyong Lai (Abstract and Applied Analysis)
A nonlinear generalization of the famous Camassa-Holm model is investigated. Provided that initial value and satisfies an associated sign condition, it is shown that there exists a unique global weak solution to the equation in space in the sense of distribution, and .